A RANDOMIZED CONTROLLED TRIAL ON THE EFFECTIVENESS OF COGNITIVE BEHAVIORAL THERAPY AND PAROXETINE VS. PAROXETINE IN PANIC DISORDER: LONGITUDINAL FOLLOW-UP WITH NEUROPHYSIOLOGICAL CORRELATES WITHIN AN INNOVATIVE FRAMEWORK - D, MOHANAAPRIYA; VENKATRAMAN; SHRINE, DHEEPTHA; GOVINDAN, LAKSHMANAN (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Background: Panic Disorder (PD) is a common and disabling anxiety disorder characterized by recurrent, unexpected panic attacks and persistent concern about their recurrence or consequences. It affects a significant proportion of the population, often leading to marked impairment in social, occupational, and daily functioning. PD typically emerges in early adulthood and may be accompanied by agoraphobia, increasing the severity and complexity of clinical presentation. Early and effective intervention is crucial to reduce the risk of chronicity and comorbid psychiatric conditions, such as depression and substance use disorders. Pharmacological treatment is a cornerstone in the management of PD, with Selective Serotonin Reuptake Inhibitors (SSRIs), such as paroxetine, being widely recognized as first-line agents due to their efficacy and safety profile. These medications help reduce the frequency and intensity of panic attacks and alleviate anticipatory anxiety and phobic avoidance. However, some patients exhibit partial response or residual symptoms, necessitating augmentation strategies to optimize outcomes and promote recovery. Cognitive Behavioral Therapy (CBT) is a well-established, evidence-based psychotherapy for PD, targeting maladaptive thought patterns and avoidance behaviors that sustain the disorder. While both CBT and pharmacotherapy are individually effective, there is limited research on the long-term effectiveness of their combination, especially in routine clinical settings. Exploring the synergistic potential of combined treatment could offer valuable insights into sustained symptom remission, functional recovery, and relapse prevention, informing future clinical guidelines and personalized treatment approaches. Objective: This study evaluates the effectiveness of CBT combined with paroxetine versus paroxetine alone in PD treatment, assessing both clinical and neurophysiological correlates over a 6-month follow-up. Methods: A randomized controlled trial (RCT) with 60 participants diagnosed with PD per DSM-5 criteria was conducted. Participants were randomized into two groups: (1) CBT + Paroxetine (n=30) and (2) Paroxetine only (n=30). The primary outcome was symptom reduction on the Panic Disorder Severity Scale (PDSS) and the Hamilton Anxiety Rating Scale (HAM-A). Secondary outcomes included heart rate variability (HRV) and electroencephalogram (EEG) markers of treatment response. Assessments were conducted at baseline, 6 weeks, and 12 weeks, with follow-up at 6 months. Results: The CBT + Paroxetine group showed significantly greater reductions in PDSS and HAM-A scores compared to the Paroxetine-only group at 12 weeks (p<0.05). Neurophysiological measures indicated increased HRV and normalization of EEG patterns in the combination group. At 6 months, the relapse rate was lower in the CBT + Paroxetine group (20%) than in the Paroxetine-only group (40%). Conclusion: Adding CBT to paroxetine improves symptom control, enhances neurophysiological responses, and reduces relapse rates in PD patients. These findings support the integration of psychotherapy with pharmacotherapy for optimizing long-term PD management.